2002
DOI: 10.1046/j.1365-313x.2002.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐dependent transcriptional activation of novel repetitive elements during cold acclimation of alfalfa (Medicago sativa)

Abstract: SummaryIn a search for cold-regulated genes that are differentially expressed in alfalfa genotypes of contrasting freezing tolerance, we screened 1036 arrayed cDNA clones. The screening resulted in isolation of cDNA clones, which demonstrated dramatic differences in expression between hardy and un-hardy alfalfa varieties. Detailed analysis revealed that these cDNAs represent parts of novel non-coding repetitive elements carrying long-terminal repeats (LTR) and other retroelement-like features. Despite strong e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Rocha et al (2005) found three mRNA transcript fragments, over expressed in wheat roots treated with DON, with full or partial homology to retrotransposons. This and other researches (Ivashuta et al 2002) implies the possibility of genetic or epigenetic transposon activation in plant cells in response to stress. Therefore, Fadl-Allah et al (2007) and Mohammed et al (2008) speculated that the existed variation of DNA which have been detected by RAPD-PCR after treating with DON and AFB 1 might be a DNA structural changes, which indicated their genotoxic effect on wheat.…”
Section: Resultsmentioning
confidence: 85%
“…Rocha et al (2005) found three mRNA transcript fragments, over expressed in wheat roots treated with DON, with full or partial homology to retrotransposons. This and other researches (Ivashuta et al 2002) implies the possibility of genetic or epigenetic transposon activation in plant cells in response to stress. Therefore, Fadl-Allah et al (2007) and Mohammed et al (2008) speculated that the existed variation of DNA which have been detected by RAPD-PCR after treating with DON and AFB 1 might be a DNA structural changes, which indicated their genotoxic effect on wheat.…”
Section: Resultsmentioning
confidence: 85%
“…The level of transcript activation was genotype-specific. This and other research (Ivashuta et al 2002) implies that there may be genetic or epigenetic transposon activation in plant cells in response to stress and the degree of activation may be genotype-specific (perhaps due to genotype-specific sites of genomic integration). Even if they are transpositionally inactive, the transcription of redundant RNA could affect the expression of other genes through RNA-RNA interaction or RNA-directed DNA methylation (Grant 1999, Wolffe andMatzke 1999).…”
Section: Activation Of Wheat Retrotransposon-like Transcriptsmentioning
confidence: 86%
“…In previous research, Rocha et al (2005) found three mRNA transcript fragments, over expressed in wheat roots treated with DON, with full or partial homology to retrotransposons. This and other research (Ivashuta et al 2002) implies that there may be genetic or epigenetic transposon activation in plant cells in response to stress. The present cytological results might indicate that DON as a toxicant might evoke the flower organ dysfunction by interfering with normal gene regulation responsible for meiotic chromosome division.…”
Section: Mw (Bp)mentioning
confidence: 77%